GYMNASTICS FOR ALL: DIFFERENT CULTURES, DIFFERENT PERSPECTIVES - Daniela Bento-Soares; Laurita Marconi Schiavon (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
Gymnastics for All (GfA) is a physical activity whose boundaries are not clearly defined from an institutional perspective. Thus, it is necessary to understand the conception adopted in GfA and its value for each social group. This study aims to discuss how different National Governing Bodies (NGB) of Gymnastics approach GfA. We asked 44 NGBs, represented by general administrative and/or GfA-specific members, about the definition of GfA adopted by the countries they represent. We used an online questionnaire hosted on Google Forms®, in four languages. The answers were analyzed through Content Analysis, whose categories were created based on a mixed model. Its strategy adopted an iterative construction of an explanation. Although similar principles of GfA can be found in different definitions, the results of the questionnaire showed that GfA means different things to each social group, so it is difficult to discuss one single understanding. Rather, it is more reasonable to think of GfA as a set of understandings. We understand that the value of GFA resides precisely in this wide variety of meanings and in the life-long practice of Gymnastics.